Ceci n'est pas une copie : design between innovation and imitation - Meplon, Chris, ....- (Tielt : Lannoo, 2016)
"Innovation or imitation: rarely a black-and-white issue." Copying is bad. Gaining wealth or fame with someone else's creative work is morally reprehensible, and in principle forbidden by law. But are things really that clear-cut? Sometimes a copy – or something greatly resembling a copy – comes from an unexpected source. Sometimes it can even lead to surprising and liberating new insights. Is it then still substandard, a case of parroting something else, of shameless and unfair competition? Ceci n'est pas une copie sets out in search of the nature, significance and acceptance of copying strategies in contemporary design practice. This isn't entirely obvious, because we are touching on a sensitive topic. Designers do not always see the efforts of competitors who copy them as a form of flattery. In reality, they fear loss of income and damaged reputations.